INVESTIGATION INTO AI-ASSISTED OPTIMIZATION OF THIN-WALLED CROSS-SECTIONS - Movchan, Oleksandr (Sworld-Us Conference proceedings, 2025)
This research reviews the integration of artificial intelligence in structural cross-section selection, highlighting supervised learning, reinforcement learning, evolutionary algorithms, and physics-informed models as complementary methodologies. Supervis